(untitled) (ModaPalavra e-periódico, 2020)
From a postcolonial / decolonial perspective, the purpose of the article is to question the western concept of fashion and its possible uses. We understand that the concept of fashion can be used as a notion within the colonial ideological apparatus that seeks to disallow the relationship of non - western societies with time by stating that the latter has no fashion because little change their clothing, or as the colonizer prefers to call it, your costume. This type of binary, in the case of “fashion X costume”, engenders, as Quijano (2005) points out, non - Western societies and provides the West with the ideological status of the movement, its ability to change, renew itself and, w hy not, evolve (in an evolutionary sense). As Said (2007) points out, the colonizer, in his place of authority, understands that it is up to him to “read” the colonized and to translate his culture to himself